Method for manufacturing a solid battery and solid battery
Patent Information
- Application Number
- JP2025059478
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0020】 本発明によれば、負極活物質として、シリコン系活物質を使用し、負極合剤層のプレドープ率が低くても、初回クーロン効率を高くすることが可能な固体電池の製造方法を提供することができる。
Smart Images

Figure 2026166507000004 
Figure 2026166507000005 
Figure 2026166507000001
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for manufacturing a solid-state battery and to a solid-state battery. [Background technology]
[0002] In recent years, research and development has been conducted on solid-state batteries that contribute to energy efficiency, in order to ensure that more people have access to affordable, reliable, sustainable, and advanced energy.
[0003] Patent Document 1 describes a method for manufacturing a secondary battery comprising an electrolyte layer containing a solid electrolyte and a negative electrode containing a negative electrode active material. In this method, the negative electrode in a laminate of a current collector / negative electrode or a laminate of a current collector / positive electrode / electrolyte / negative electrode is brought into contact with a lithium foil attached to a copper foil, and pressure is applied to pre-dope the negative electrode with lithium, after which the copper foil is peeled off. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2014-86222 [Overview of the project] [Problems that the invention aims to solve]
[0005] However, in the secondary battery described in Patent Document 1, when a silicon-based active material is used as the negative electrode active material, the initial Coulomb efficiency becomes low when the pre-doping rate of the negative electrode is low. This is presumed to be because lithium is not uniformly pre-doped into the negative electrode.
[0006] The present invention aims to provide a method for manufacturing a solid-state battery that uses a silicon-based active material as the negative electrode active material and can achieve high initial Coulomb efficiency even with a low pre-doping rate in the negative electrode mixture layer. [Means for solving the problem]
[0007] (1) A method for producing a solid-state battery, comprising: a step of forming a lithium film on a copper foil; a step of applying a slurry containing a silicon-based active material on the lithium film to form a negative electrode mixture layer precursor; a step of forming a solid electrolyte layer on the negative electrode mixture layer precursor to obtain a laminate; and a step of pressurizing the laminate to form a negative electrode mixture layer, wherein the pressure for pressurizing the laminate is 30 MPa or more.
[0008] (2) The method for producing a solid-state battery according to (1), wherein the copper foil has a thickness of 5 μm or more and 100 μm or less.
[0009] (3) The method for producing a solid-state battery according to (1) or (2), wherein the lithium film has a thickness of 1 μm or more and 30 μm or less.
[0010] (4) The method for producing a solid-state battery according to any one of (1) to (3), wherein the negative electrode mixture layer precursor has a thickness of 10 μm or more and 200 μm or less.
[0011] (5) The method for producing a solid-state battery according to any one of (1) to (4), wherein the lithium film is formed on the copper foil by a vapor deposition method.
[0012] (6) The method for producing a solid-state battery according to any one of (1) to (5), wherein the slurry further contains a solid electrolyte.
[0013] (7) The method for producing a solid-state battery according to (6), wherein the solid electrolyte is a sulfide solid electrolyte.
[0014] (8) The method for producing a solid-state battery according to (7), wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
[0015] (9) The method for producing a solid-state battery according to any one of (1) to (8), wherein the slurry contains a solvent.
[0016] (10) The method for producing a solid-state battery according to (9), wherein the solvent has a boiling point of 120°C or higher.
[0017] (11) A method for manufacturing a solid battery according to any one of (1) to (10), wherein the solid electrolyte layer comprises a sulfide solid electrolyte.
[0018] (12) The method for manufacturing a solid battery according to (11), wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
[0019] (13) A solid battery manufactured by a method for manufacturing a solid battery, comprising the steps of: forming a lithium film on copper foil; applying a slurry containing a silicon-based active material to the lithium film to form a negative electrode mixture layer precursor; forming a solid electrolyte layer on the negative electrode mixture layer precursor to obtain a laminate; and pressurizing the laminate to form a negative electrode mixture layer. [Effects of the Invention]
[0020] According to the present invention, it is possible to provide a method for manufacturing a solid-state battery that uses a silicon-based active material as the negative electrode active material and can achieve high initial Coulomb efficiency even with a low pre-doping rate of the negative electrode mixture layer. [Brief explanation of the drawing]
[0021] [Figure 1] This figure shows the initial charge-discharge curve of the half-cell in Example 1. [Figure 2] This figure shows the initial charge-discharge curve of the half-cell in Comparative Example 1. [Modes for carrying out the invention]
[0022] Embodiments of the present invention will be described below.
[0023] [Manufacturing method for solid-state batteries] The manufacturing method for the solid-state battery of this embodiment includes the steps of: forming a lithium film on copper foil; applying a slurry containing a silicon-based active material to the lithium film to form a negative electrode mixture layer precursor; forming a solid electrolyte layer on the negative electrode mixture layer precursor to obtain a laminate; and pressurizing the laminate to form a negative electrode mixture layer. At this time, the pressure applied to the laminate is 30 MPa or more, preferably 50 MPa or more, and more preferably 250 MPa or more. When the pressure applied to the laminate is 30 MPa or more, the initial Coulomb efficiency of the solid-state battery is high even if the pre-doping rate of the negative electrode mixture layer is low. This is because lithium is uniformly pre-doped into the negative electrode mixture layer. The pressure applied to the laminate is, for example, 300 MPa or less.
[0024] In this case, the time for pressurizing the laminate is not particularly limited, but for example, it is 1 hour or more. Also, the temperature when pressurizing the laminate is not particularly limited, but for example, it is 25°C to 60°C. Furthermore, the pre-doping rate (molar ratio of Li to Si) of the negative electrode mixture layer is not particularly limited, but for example, it is 0.3 to 1.2.
[0025] Furthermore, after obtaining the laminate, the copper foil may be peeled off, or it may be used as the negative electrode current collector of a solid-state battery without peeling off the copper foil.
[0026] The thickness of the copper foil is preferably 5 μm to 100 μm, and more preferably 10 μm to 30 μm. When the thickness of the copper foil is 5 μm or more, the copper foil is less likely to warp when the laminate is pressed, and lithium is more easily pre-doped uniformly into the negative electrode mixture layer precursor. On the other hand, when the thickness of the copper foil is 100 μm or less, when the laminate is pressed, the pressure is applied uniformly regardless of the part of the laminate, and lithium is more easily pre-doped uniformly into the negative electrode mixture layer precursor.
[0027] The thickness of the lithium film is preferably 1 μm or more and 30 μm or less, and more preferably 3 μm or more and 10 μm or less. When the lithium film thickness is 1 μm or more, lithium is more easily pre-doped into the negative electrode mixture layer precursor by a predetermined amount. On the other hand, when the lithium film thickness is 30 μm or less, lithium is less likely to be excessively pre-doped into the negative electrode mixture layer precursor.
[0028] The method for depositing a lithium film on copper foil is not particularly limited, as long as it is possible to deposit a lithium film with a thickness of 1 μm or more and 30 μm or less, but one example is vapor deposition.
[0029] The thickness of the negative electrode mixture layer precursor is preferably 10 μm or more and 200 μm or less, and more preferably 10 μm or more and 50 μm or less. When the thickness of the negative electrode mixture layer precursor is 10 μm or more, lithium is more easily pre-doped into the negative electrode mixture layer precursor by a predetermined amount, and the initial Coulomb efficiency tends to be higher. On the other hand, when the thickness of the negative electrode mixture layer precursor is 200 μm or less, lithium is more easily pre-doped into the negative electrode mixture layer precursor uniformly, regardless of the location in the laminate, and the initial Coulomb efficiency tends to be higher.
[0030] The thickness of the negative electrode mixture layer is not particularly limited, but for example, it is 10 μm or more and 50 μm or less.
[0031] The silicon content in the silicon-based active material in the solid component constituting the slurry is preferably 50% by mass or more and 80% by mass or less, and more preferably 50% by mass or more and 70% by mass or less. When the silicon content in the silicon-based active material in the solid component constituting the slurry is 50% by mass or more and 80% by mass or less, lithium is more easily pre-doped into the negative electrode mixture layer precursor.
[0032] Furthermore, the silicon-based active material is preferably a composite material of silicon and an element other than silicon (silicon-based composite material). The silicon-based composite material is not particularly limited as long as it is capable of intercalating and releasing lithium ions, but examples include silicon / carbon composite materials, silicon / nitrogen composite materials, silicon / titanium composite materials, silicon / aluminum composite materials, silicon / lithium composite materials, and silicon / copper composite materials.
[0033] The slurry preferably further contains a solid electrolyte. This facilitates the pre-doping of lithium into the negative electrode mixture layer precursor and increases the initial Coulomb efficiency of the solid-state battery.
[0034] The solid electrolyte is not particularly limited as long as it can conduct lithium ions, but examples include oxide solid electrolytes and sulfide solid electrolytes. Among these, sulfide solid electrolytes are preferred because they facilitate the pre-doping of lithium into the negative electrode mixture layer precursor and increase the initial Coulombic efficiency of the solid-state battery, and argyrodite-type sulfide solid electrolytes are particularly preferred.
[0035] The sulfide solid electrolyte contained in the solid electrolyte layer includes, for example, a metal element (M) that acts as a conductive ion and sulfur (S). Examples of M include Li, Na, K, Mg, and Ca. Among these, Li is preferred.
[0036] The sulfide solid electrolyte preferably contains Li, A (one or more elements selected from the group consisting of P, Si, Ge, Al, and B), and S, and more preferably Li and P. Furthermore, the sulfide solid electrolyte may further contain halogen elements (e.g., Cl, Br, I) from the viewpoint of ionic conductivity. The sulfide solid electrolyte may also further contain O.
[0037] Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga or In), Li v P w S x Cl y Br z (v, w, x, y, z>0). Among these, from the viewpoint of ionic conductivity, Li v P w S x Cl y Br z (v, w, x, y, z>0) is preferred, and Li v P w S x Cl y Br z (0<v<10, 0<w<5, 0<x<5, 0<y<5, 0<z<5) is more preferred, and examples thereof include Li 5.4 PS 4.4 Cl 0.8 Br 0.8 .
[0038] Note that, for example, the description of "Li2S-P2S5" means a sulfide solid electrolyte obtained using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.
[0039] Furthermore, the sulfide solid electrolyte may be sulfide glass or crystalline sulfide glass, or a crystalline material obtained by a solid-phase method. Sulfide glass can be obtained, for example, by performing a mechanical milling method (for example, a method of milling using a ball mill) on the raw material composition. Crystalline sulfide glass can be obtained, for example, by heat-treating sulfide glass at a temperature above its crystallization temperature.
[0040] The sulfide solid electrolyte contained in the solid electrolyte layer is preferably an argyrodite-type sulfide solid electrolyte. A sulfide solid electrolyte is preferred, and an argyrodite-type sulfide solid electrolyte is particularly preferred, because it facilitates lithium predoping of the negative electrode mixture layer precursor and increases the initial Coulomb efficiency of the solid-state battery.
[0041] The median diameter of the solid electrolyte is preferably between 100 nm and 1000 nm, and more preferably between 100 nm and 700 nm. When the median diameter of the solid electrolyte is 100 nm or more, aggregation of the solid electrolyte is suppressed, and when it is 1000 nm or less, aggregation of the silicon-based active material is suppressed.
[0042] The solid electrolyte content in the solid components of the slurry is preferably 10% by mass or more and 50% by mass or less, and more preferably 20% by mass or more and 50% by mass or less. When the solid electrolyte content in the solid components of the slurry is 10% by mass or more and 50% by mass or less, lithium is more easily pre-doped into the negative electrode mixture layer precursor.
[0043] The slurry may further contain a binder. The binder is not particularly limited, but examples include fluororesin binders such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), and fluororubber; and non-fluororubber binders such as butadiene rubber, hydrogenated butadiene rubber, styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber, nitrile butadiene rubber, hydrogenated nitrile butadiene rubber, and ethylene propylene rubber. Acrylic binders and polyimide binders may also be used as binders. The binder content in the solid components constituting the slurry is not particularly limited, but for example, it is 0.5% by mass or more and 3% by mass or less.
[0044] The slurry may further contain a conductive additive. The conductive additive is not particularly limited, but examples include acetylene black, metallic carbon nanotubes (MCNTs), and semiconducting carbon nanotubes (SCNTs). The content of the conductive additive in the solid components constituting the slurry is not particularly limited, but for example, it is 0.05% by mass or more and 5% by mass or less.
[0045] The slurry preferably further contains a solvent. This facilitates uniform pre-doping of the lithium into the negative electrode mixture layer precursor.
[0046] The boiling point of the solvent may be 120°C or higher, or 140°C or higher. A boiling point of 120°C or higher makes it easier to obtain a negative electrode compound layer precursor of a predetermined thickness, which tends to increase the initial Coulomb efficiency of the solid-state battery. For example, the boiling point of the solvent is 200°C or lower.
[0047] The solvent having a boiling point of 120°C or higher is not particularly limited, but examples include butyl butyrate (boiling point 166°C), o-xylene (boiling point 144°C), m-xylene (boiling point 139°C), p-xylene (boiling point 138°C), and decane (boiling point 174°C). Among these, butyl butyrate is preferred because it facilitates uniform pre-doping of the negative electrode mixture layer precursor with lithium.
[0048] The solid electrolyte constituting the solid electrolyte layer is not particularly limited, but examples include sulfide solid electrolytes and oxide solid electrolytes. Among these, sulfide solid electrolytes are preferred from the viewpoint of the initial Coulomb efficiency of the solid-state battery, and argyrodite-type sulfide solid electrolytes are particularly preferred.
[0049] The form of the solid electrolyte is not particularly limited, but for example, particles can be used.
[0050] The solid electrolyte content in the solid electrolyte layer is not particularly limited, but is, for example, 50% by mass or more and 99% by mass or less.
[0051] The solid electrolyte layer may further contain a binder or the like.
[0052] The thickness of the solid electrolyte layer is not particularly limited, but is, for example, between 10 μm and 600 μm.
[0053] The method for forming the solid electrolyte layer is not particularly limited, but one example is a method of press-molding a composition containing a solid electrolyte.
[0054] The laminate is not particularly limited, but as long as copper foil, lithium film, anode composite layer precursor, and solid electrolyte layer are sequentially laminated, examples include copper foil / lithium film / anode composite layer precursor / solid electrolyte layer laminate, copper foil / lithium film / anode composite layer precursor / solid electrolyte layer / cathode composite layer laminate, and copper foil / lithium film / anode composite layer precursor / solid electrolyte layer / cathode composite layer / cathode current collector laminate.
[0055] Solid-state batteries are not particularly limited, but examples include all-solid-state lithium-ion secondary batteries and semi-solid-state lithium-ion secondary batteries.
[0056] The following describes an example of a manufacturing method for an all-solid-state lithium-ion secondary battery when using a copper foil / lithium film / negative electrode mixture layer precursor / solid electrolyte layer laminate as the laminate.
[0057] The copper foil / lithium film / negative electrode mixture layer precursor / solid electrolyte layer laminate is pressurized to form a lithium-predoped negative electrode mixture layer, thereby obtaining a copper foil / negative electrode mixture layer / solid electrolyte layer laminate. Next, the copper foil is peeled off from the copper foil / negative electrode mixture layer / solid electrolyte layer laminate to obtain a negative electrode mixture layer / solid electrolyte layer laminate. Then, a positive electrode mixture layer and a positive electrode current collector are sequentially laminated on the side of the negative electrode mixture layer / solid electrolyte layer laminate where the solid electrolyte layer is formed, thereby obtaining a negative electrode mixture layer / solid electrolyte layer laminate / positive electrode mixture layer / positive electrode current collector laminate. Furthermore, a negative electrode current collector is formed on the side of the negative electrode mixture layer / solid electrolyte layer laminate / positive electrode mixture layer / positive electrode current collector laminate where the negative electrode mixture layer is formed, thereby obtaining an all-solid-state lithium-ion secondary battery.
[0058] The order in which each layer is formed in the negative electrode mixture layer / solid electrolyte layer laminate is not particularly limited. Furthermore, when obtaining an all-solid-state lithium-ion secondary battery, chemical conversion may be performed as needed.
[0059] The materials that make up the negative electrode current collector are not particularly limited, but examples include silver, palladium, gold, platinum, aluminum, copper, nickel, stainless steel, and carbon. Among these, copper, stainless steel, and nickel are preferred from the viewpoint of conductivity and cost.
[0060] The shape of the negative electrode current collector is not particularly limited, but examples include foil-like, plate-like, mesh-like, non-woven fabric-like, and foam-like forms.
[0061] The positive electrode composite layer contains a positive electrode active material. The positive electrode active material is not particularly limited, but examples include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), and LiNi p Mn q Co r O2(p+q+r=1), LiNi p Al q Co r O2 (p+q+r=1), lithium manganese (LiMn2O4), Li 1+x Mn 2-x-y M y Examples include O4(x+y=2) (where M is one or more elements selected from the group consisting of Al, Mg, Co, Fe, Ni, and Zn), lithium titanate, and LiMPO4 (where M is one or more elements selected from the group consisting of Fe, Mn, Co, and Ni).
[0062] The content of the positive electrode active material in the positive electrode composite layer is not particularly limited, but for example, it is 50% by mass or more and 99% by mass or less.
[0063] The positive electrode composite layer may further contain a solid electrolyte. The solid electrolyte is not particularly limited as long as it is capable of conducting lithium ions, but examples include oxide solid electrolytes and sulfide solid electrolytes.
[0064] The positive electrode composite layer may further contain a binder, a conductive additive, and the like.
[0065] The method for forming the positive electrode composite layer is not particularly limited, but one example is a method of applying a slurry containing a positive electrode active material and a solvent.
[0066] The materials used to constitute the positive electrode current collector are not particularly limited, but examples include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium. Among these, aluminum, aluminum alloys, and stainless steel are preferred.
[0067] The shape of the positive electrode current collector is not particularly limited, but examples include foil-shaped and plate-shaped.
[0068] Although embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and the above embodiments may be modified as appropriate within the scope of the spirit of the present invention. [Examples]
[0069] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.
[0070] [Example 1] (Vapor deposition) Using a vacuum deposition apparatus, a lithium film with a thickness of 6.5 μm was deposited on a copper foil with a thickness of 10 μm to obtain a substrate for pre-doping.
[0071] The slurry, copper foil / lithium film / anode mixture layer precursor laminate, solid electrolyte layer, and half-cell were fabricated in a glove box purged with argon as follows.
[0072] (Slurry manufacturing) Using a rotation / revolution mixer, 70 parts by mass of silicon / carbon composite material and median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 29 parts by mass of ) were mixed. Next, 1 part by mass of polyvinylidene fluoride (PVDF) and butyl butyrate were added, and the mixture was mixed using a rotation-revolution mixer. After that, the mixture was dispersed using an ultrasonic homogenizer to obtain a slurry. Here, butyl butyrate has a boiling point of 166°C.
[0073] (Manufacturing of copper foil / lithium film / negative electrode mixture layer precursor laminate) Using an applicator, a slurry was applied onto a lithium film on a pre-doping substrate and dried to form a 20 μm thick negative electrode mixture layer precursor. This was then punched out to obtain a copper foil / lithium film / negative electrode mixture layer precursor laminate. During this process, the laminate was dried at 40°C for 30 minutes, followed by drying at 60°C for 30 minutes.
[0074] (Manufacturing of solid electrolyte layer) Median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4 PS 4.4 Cl 0.8 Br 0.8 The material was press-molded at a pressure of 145 MPa to obtain a solid electrolyte layer.
[0075] (Half-cell manufacturing) A solid electrolyte layer, indium foil, and lithium foil were sequentially placed on the negative electrode mixture layer precursor of a copper foil / lithium film / negative electrode mixture layer precursor laminate. Under conditions of 25°C and 60 MPa pressure, the laminate was pressurized for 3 days to form a 25 μm thick lithium-predoped negative electrode mixture layer. After that, the copper foil was peeled off to obtain a half-cell. At this time, no lithium film was present on the surface of the negative electrode mixture layer, and the pre-doping rate (molar ratio of Li to Si) of the negative electrode mixture layer was 0.56.
[0076] [Comparative Example 1] Copper foil / negative electrode composite layer laminates, solid electrolyte layers, and half-cells were fabricated in a glove box purged with argon as follows.
[0077] (Manufacturing of copper foil / negative electrode composite layer laminates) Using an applicator, the slurry was applied to a 10 μm thick copper foil, which served as the negative electrode current collector, in the same manner as in Example 1. After drying, a 20 μm thick negative electrode mixture layer was formed, and then the material was punched out to obtain a copper foil / negative electrode mixture layer laminate.
[0078] (Manufacturing of solid electrolyte layer) Median diameter (D 50 ) 700nm argyrodite-type sulfide solid electrolyte (Li 5.4PS 4.4 Cl 0.8 Br 0.8 The material was press-molded at a pressure of 145 MPa to obtain a solid electrolyte layer.
[0079] (Half-cell manufacturing) A half-cell was obtained by sequentially placing a solid electrolyte layer, indium foil, and lithium foil on the negative electrode mixture layer of a copper foil / negative electrode mixture laminate, and then pressurizing it for 3 days under conditions of 25°C and 60 MPa.
[0080] [Initial Coulomb Efficiency] Charge and discharge tests were conducted on half-cells of Example 1 and Comparative Example 1. Specifically, half-cells consisting of a negative electrode mixture layer / indium foil / lithium foil laminate were fabricated, and the initial Coulomb efficiency (ratio of initial discharge capacity to initial charge capacity) was evaluated. Figures 1 and 2 show the initial charge and discharge curves of the half-cells of Example 1 and Comparative Example 1.
[0081] Figure 2 shows a steep slope near 0 mAh in the initial discharge curve, whereas Figure 1 does not show a similar steep slope near 0 mAh / g in the initial discharge curve. This is because lithium is pre-doped into the negative electrode mixture layer of the half-cell in Example 1.
[0082] Table 1 shows the evaluation results of the initial Coulomb efficiency of the half-cell.
[0083] [Table 1]
[0084] Table 1 shows that the half-cell of Example 1 has a high initial Coulombic efficiency even with a low pre-doping rate. In contrast, the half-cell of Comparative Example 1 has a low initial Coulombic efficiency because the negative electrode mixture layer is not pre-doped.
[0085] (Cross-sectional SEM image) Using a scanning electron microscope (SEM), cross-sections (1000x magnification) at three locations in the half-cells of Example 1 and Comparative Example 1 were observed. As a result, it was confirmed that the average thickness of the negative electrode mixture layer at three locations in Example 1 (17 μm) was greater than the average thickness of the negative electrode mixture layer at three locations in Comparative Example 1 (10 μm). This is because lithium was pre-doped into the negative electrode mixture layer of Example 1.
[0086] Furthermore, the composition of the negative electrode mixture layer in the cross-sectional SEM images of the half-cells of Example 1 and Comparative Example 1 was analyzed using an energy-dispersive X-ray fluorescence analyzer (EDX) attached to the SEM. Specifically, the content of elements (Si, F, P, S, Cl, Br) in the upper, middle, and lower parts of the negative electrode mixture layer in three cross-sections was analyzed by dividing it into three equal-area sections in the thickness direction. Next, the mean value and standard deviation of the content in nine regions for each element were determined, and then the coefficient of variation was calculated by dividing the standard deviation by the mean value.
[0087] Tables 2 and 3 show the analysis results of the composition of the negative electrode mixture layer in the cross-sectional SEM images of half-cells from Example 1 and Comparative Example 1.
[0088] [Table 2]
[0089] [Table 3]
[0090] From Tables 2 and 3, the negative electrode mixture layer of Example 1 had a smaller coefficient of variation for Si, F, P, S, Cl, and Br than the negative electrode mixture layer of Comparative Example 1, and regardless of the measurement location, silicon / carbon composite material, PVDF, and Li 5.4 PS 4.4 Cl 0.8 Br 0.8 It can be seen that they are present uniformly. Here, Si comes from the silicon / carbon composite material, F comes from PVDF, and P, S, Cl and Br come from Li 5.4 PS4.4 Cl 0.8 Br 0.8 This is thought to be the origin of the lithium. Therefore, it can be seen that lithium is uniformly pre-doped into the negative electrode mixture layer of Example 1.
Claims
1. The process involves forming a lithium film on copper foil, The process involves applying a slurry containing a silicon-based active material onto the lithium film to form a negative electrode mixture layer precursor, The process of forming a solid electrolyte layer on the negative electrode mixture precursor to obtain a laminate, The process includes the step of pressurizing the laminate to form a negative electrode mixture layer, A method for manufacturing a solid battery, wherein the pressure applied to the laminate is 30 MPa or more.
2. The method for manufacturing a solid battery according to claim 1, wherein the copper foil has a thickness of 5 μm or more and 100 μm or less.
3. The method for manufacturing a solid battery according to claim 1 or 2, wherein the lithium film has a thickness of 1 μm or more and 30 μm or less.
4. The method for manufacturing a solid battery according to claim 1 or 2, wherein the negative electrode mixture layer precursor has a thickness of 10 μm or more and 200 μm or less.
5. A method for manufacturing a solid battery according to claim 1 or 2, wherein a lithium film is formed on the copper foil by a vapor deposition method.
6. The method for manufacturing a solid battery according to claim 1 or 2, wherein the slurry further comprises a solid electrolyte.
7. The method for manufacturing a solid battery according to claim 6, wherein the solid electrolyte is a sulfide solid electrolyte.
8. The method for manufacturing a solid battery according to claim 7, wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
9. The method for producing a solid battery according to claim 1 or 2, wherein the slurry contains a solvent.
10. The method for manufacturing a solid battery according to claim 9, wherein the solvent has a boiling point of 120°C or higher.
11. The method for manufacturing a solid battery according to claim 1 or 2, wherein the solid electrolyte layer comprises a sulfide solid electrolyte.
12. The method for manufacturing a solid battery according to claim 11, wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
13. A solid-state battery manufactured by a method for manufacturing a solid-state battery, comprising the steps of: forming a lithium film on copper foil; applying a slurry containing a silicon-based active material to the lithium film to form a negative electrode mixture layer precursor; forming a solid electrolyte layer on the negative electrode mixture layer precursor to obtain a laminate; and pressurizing the laminate to form a negative electrode mixture layer.
Citation Information
Patent Citations
Method for manufacturing secondary battery
JP2014086222A